Autoantibodies against galectin-2 peptides as biomarkers for the antiphospholipid syndrome - Janko, Christina; Schiller, Martin (Lupus, 2012)
Autoantibodies against opsonins of dying and dead cells mediate Fcγ receptor-dependent phagocytosis of autologous apoptotic and necrotic cells and hereby tend to elicit inflammation instead of silent clearance. We analysed sera of patients with chronic autoimmune diseases for the occurrence of IgG autoantibodies recognizing galectins. These pluripotent effectors can also bind to apoptotic or necrotic cells. Patients with antiphospholipid syndrome (APS; n = 104) and systemic lupus erythematosus (SLE; n = 62) were examined, healthy donors (n = 31) served as controls. Selected peptides of galectin (Gal)-2 were employed for peptide-based ELISAs. Levels of anti-Gal-2PEP-IgG were significantly increased in SLE and APS when compared with controls. In addition, patients with APS showed significantly higher levels of anti-Gal-2PEP-IgG compared with patients with SLE. Anti-Gal-2PEP-IgG may, therefore, be considered novel biomarkers for APS.